Analysis of Early Childhood Social-Emotional Development Using the EMC2 Approach in Early Childhood Education Institutions - Mushab Al Umairi; Alfiyanti Nurkhasyanah; Abdul Razak Masae (Aulad: Journal on Early Childhood, 2026)
Children's inability to manage their social and emotional well-being requires strategic intervention through adult support. This study aims to analyze the social and emotional development of early childhood through the implementation of the EMC2 approach in the PAUD environment. This study employed a field research design with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis was conducted narratively to describe the opinions, actions, and phenomena observed during the study. Theoretically, this study confirms that the EMC2 approach is effective in mapping and stimulating children's emotional intelligence in formal settings. Practically, the high percentage of students in the "Developing" category (74% cumulative BSH and BSB) indicates that integrating teachers' understanding of children's developmental stages and structured adult support can minimize social-emotional barriers. These results imply the importance of standardizing teacher competencies in emotional literacy to ensure that the remaining percentage of "Undeveloped" children can be accommodated through more personalized interventions.